Effect of seed treatment with biostimulants and fungicide on development and yield potential of spring wheat - Pille Sooväli; Tiia Kangor; Mati Koppel (Agraarteadus, 2018)

(untitled)
In the years 2013–2014, the Estonian Crop Research Institute conducted a field trial in order to investigate the effect of seed treatment with seaweed based biostimulants and fungicide on spring wheat (Triticum aestivum L.). Seed treatments of the varieties 'Specifik' and 'Uffo' were used with (fludioxonil + cyproconazole) and without fungicide (biostimulants Raykat Start, Fertigrain Start) and mixture (fludioxonil + cyproconazole + Fertigrain Start), and untreated seed as the control were evaluated. The objective of this study was to assess the development, growth and yield potential of spring wheat under the action of biostimulants, with the presence and absence of treatment of seed with fungicide. In the laboratory, we measured: 1) the length of roots and shoots of germinated seed, 2) total number and total weight of grains per ear, 3) one kernel weight per ear. In the field, we evaluated: 4) plant height, 5) the number of generative tillers that were counted in one linear meter at physiological maturity. Results showed that the application of biostimulants and fungicide for seed treatment influence the wheat early development and growth of radicle. They can increase the root length however the biostimulants and fungicide can have an opposite effect on germination of wheat seed. They can decrease the length of the first true leaf emerged from coleoptile. We noticed that seed treatment with Raykat Start increased significantly (p ≤ 0.05) the plant height of variety 'Specifik' compared to untreated. There was tendency that by using both biostimulants for seed treatment of variety 'Specifik' more generative tillers emerged, but this was not significant compared with untreated. The results suggested that solely the seed treatment with biostimulants and fungicides, there was no effect on total grain number and total grain weight per ear of wheat varieties.